Bimbingan Kelas Besar Berbasis Tazkiyatun Nafs melalui Terapi Muhasabah dan Naratif bagi Mahasantri Asrama - Yunita Embong Bulan; Dewi Indriani; Nasywa Dewi Mulyanti; Fitri Nur Indah Silmiah; Wardah Nazihah; Desi Rismala Sari; Rudy Hadi Kusuma (PENDIMAS: Jurnal Pengabdian Masyarakat, 2025)
This community service project responded to the psychological and spiritual challenges faced by female dormitory students at UINSI Samarinda, who often experience inner conflicts while living on campus. The initiative employed the Islamic concept of Tazkiyatun Nafs, integrating muhasabah therapy and narrative therapy within a large-group guidance format. The program aimed to help participants identify, accept, and manage inner emotional pressures through self-reflection and expressive writing. It was conducted in two sessions with 62 participants. Evaluation tools included pre-tests, post-tests, observation sheets, and immediate assessments. Results demonstrated increased self-awareness, emotional openness, and active engagement. Participants also showed a transformation in interpreting personal experiences and committed to enhancing social relationships. These findings indicate that large-group guidance based on Tazkiyatun Nafs, incorporating muhasabah and narrative therapy, is instrumental in enhancing both psychological and spiritual resilience. This model can serve as an Islamic values–based intervention to support student mental health in dormitory settings.